To find the measure of angle \(\angle JHI\), we can use the fact that the sum of the adjacent angles \(\angle GHJ\) and \(\angle JHI\) is equal to the measure of the obtuse angle \(\angle GHI\).
We know:
- \(\angle GHI = 135^\circ\)
- \(\angle GHJ = 112^\circ\)
Using the equation:
\[ \angle GHI = \angle GHJ + \angle JHI \]
Substituting the known values:
\[ 135^\circ = 112^\circ + \angle JHI \]
Now, we can isolate \(\angle JHI\):
\[ \angle JHI = 135^\circ - 112^\circ \] \[ \angle JHI = 23^\circ \]
Therefore, the measure of \(\angle JHI\) is \(23^\circ\).
So the correct response is:
23°